54.3.14 problem 14

Internal problem ID [8570]
Book : Elementary differential equations. Rainville, Bedient, Bedient. Prentice Hall. NJ. 8th edition. 1997.
Section : CHAPTER 17. Power series solutions. 17.5. Solutions Near an Ordinary Point. Exercises page 355
Problem number : 14
Date solved : Monday, January 27, 2025 at 04:16:34 PM
CAS classification : [_Gegenbauer]

\begin{align*} \left (-4 x^{2}+1\right ) y^{\prime \prime }+6 x y^{\prime }-4 y&=0 \end{align*}

Using series method with expansion around

\begin{align*} 0 \end{align*}

Solution by Maple

Time used: 0.003 (sec). Leaf size: 39

Order:=8; 
dsolve((1-4*x^2)*diff(y(x),x$2)+6*x*diff(y(x),x)-4*y(x)=0,y(x),type='series',x=0);
 
\[ y = \left (2 x^{2}+1\right ) y \left (0\right )+\left (x -\frac {1}{3} x^{3}-\frac {1}{6} x^{5}-\frac {3}{14} x^{7}\right ) y^{\prime }\left (0\right )+O\left (x^{8}\right ) \]

Solution by Mathematica

Time used: 0.003 (sec). Leaf size: 40

AsymptoticDSolveValue[(1-4*x^2)*D[y[x],{x,2}]+6*x*D[y[x],x]-4*y[x]==0,y[x],{x,0,"8"-1}]
 
\[ y(x)\to c_1 \left (2 x^2+1\right )+c_2 \left (-\frac {3 x^7}{14}-\frac {x^5}{6}-\frac {x^3}{3}+x\right ) \]